2007
DOI: 10.4103/0971-3026.32692
|View full text |Cite
|
Sign up to set email alerts
|

Retinoblastoma: A spectrum of manifestations in three cases on B-scan

Abstract: Retinoblastoma is a primary intraocular neoplasm of childhood, presenting with leukocoria.We present a spectrum of three cases. First two cases are of bilateral retinoblastoma and last case is a retinoblastoma of right eye. All cases are confirmed to be retinoblastoma on operation and consequent histopathological study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It presents in childhood as leukocoria. [ 1 – 5 7 8 ] The tumor projects from the retina into the vitreous chamber. Some tumors produce subretinal lesions and cause retinal detachment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It presents in childhood as leukocoria. [ 1 – 5 7 8 ] The tumor projects from the retina into the vitreous chamber. Some tumors produce subretinal lesions and cause retinal detachment.…”
Section: Methodsmentioning
confidence: 99%
“…[ 1 2 ] The tumor outline is irregular. B-scan may help in the detection of optic nerve invasion resulting from extraocular spread of the tumor[ 1 – 5 7 ] [Figures 14 and 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…The most common presentation is leukocoria or an abnormal whitish reflection from the retina of the eye of affected child. (14) USG shows echogenic lesion and calcium deposits with optic nerve involvement in many cases. In our study 2 cases of unilateral retinoblastoma were identified.…”
Section: ) Lacrimal Gland Tumoursmentioning
confidence: 99%
“…Retinoblastoma and its variants are seen in children, whereas choroidal melanomas and its variants are seen in adults. Two articles [1,2] in this issue, highlight the use of USG in these two pathologies.…”
mentioning
confidence: 99%